2022
DOI: 10.3390/cimb44100305
|View full text |Cite
|
Sign up to set email alerts
|

Classical Angiogenic Signaling Pathways and Novel Anti-Angiogenic Strategies for Colorectal Cancer

Abstract: Although productive progress has been made in colorectal cancer (CRC) researchs, CRC is the second most frequent type of malignancy and the major cause of cancer-related death among gastrointestinal cancers. As angiogenesis constitutes an important point in the control of CRC progression and metastasis, understanding the key signaling pathways that regulate CRC angiogenesis is critical in elucidating ways to inhibit CRC. Herein, we comprehensively summarized the angiogenesis-related pathways of CRC, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 169 publications
(190 reference statements)
0
9
0
Order By: Relevance
“…99 Their activation is positively associated with cell survival, angiogenesis, apoptosis, and metastasis in CRC. 100 Moreover, in CRC, the expression of NF-κB (p65) is directly associated with the expression level of HIF-1α, VEGF, and vascular invasion. 101 The NF-κB pathway promotes the expression of multiple angiogenic factors, including VEGF, PDGF-BB, CXCL1, CXCL8, MMP-2, MMP-9, COX-2, and IL-8, ulteriorly inducing tumor angiogenesis.…”
Section: Signaling Pathway In Angiogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…99 Their activation is positively associated with cell survival, angiogenesis, apoptosis, and metastasis in CRC. 100 Moreover, in CRC, the expression of NF-κB (p65) is directly associated with the expression level of HIF-1α, VEGF, and vascular invasion. 101 The NF-κB pathway promotes the expression of multiple angiogenic factors, including VEGF, PDGF-BB, CXCL1, CXCL8, MMP-2, MMP-9, COX-2, and IL-8, ulteriorly inducing tumor angiogenesis.…”
Section: Signaling Pathway In Angiogenesismentioning
confidence: 99%
“…TGM2 upregulates the expression of Wnt3a and β-catenin, whereas TM4SF1 activates the Wnt/β-catenin/c-Myc/SOX2 signaling pathway, thereby promoting angiogenesis in CRC. 100 Moreover, the COX-2/PGE2/EP4 axis, 121 notch signaling pathway, 100 c-MET/hepatocyte growth factor (HGF) signaling pathway, 122 and EPH/ephrin signaling system 123 are all related to angiogenesis in CRC. These various factors and pathways are connected and cross each other like points and lines.…”
Section: Signaling Pathway In Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to inhibiting the VEGF/VEGFR pathway, TKI drugs may also inhibit targets related to immune regulation, such as platelet-derived growth factor receptor (PDGFR), angiopoietin-2 receptor (TIE2), and colony-stimulating factor 1 receptor, and have stronger synergy with immunotherapy. [92][93][94] EGFR EGFR is a member of the epidermal growth factor receptor (HER) family, which includes HER1 (erbB1, EGFR), HER2 (erbB2, NEU), HER3 (erbB3), and HER4 (erbB4). 95,96 Studies have shown that EGFR is overexpressed or abnormally expressed in many solid tumors.…”
Section: Vegf/vegfrmentioning
confidence: 99%